Forms of Directive and Expressive Illocutionary Speech Acts on Instagram Social Media in The Captions of The @ganjar_pranowo Account and Their Implications for Indonesian Language Learning - Aistisya, Risma; Prabawa, Andi Haris (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The purpose of this research is to analyze the form of the directive and expressive illocutionary speech acts in the caption of the Instagram social media account @ganjar_pranowo and analyze its implication in Indonesian language learning. The writer wants to know the form of speech acts and their implementation in Indonesian language learning. The research technique used is descriptive qualitative with the object of this research being the form of directive and expressive illocutionary speech acts on the @ganjar_pramowo account capton. The data collection technique used is a listening technique, note capture screen (screenshot), with data analysis using qualitative analysis technique. The results of the research based on the analysis that has been done by the author show the form and use of directive and expressive illocutionary speech acts in the caption on the Instagram account @ganjar_pranowo namely there is a total of 25 data that have been analyzed, directive speech acts with a total of 9 data and expressive speech acts 16 data that has been analyzed. From the data that has been analyzed, the data that is often used by speakers to write Instagram captions on the @ganjar_pranomo account is asked with 3 data for directive speech acts and 7 data to say thank you for expressive speech acts and can be linked in the implications of argumentation texts, namely structure, content, and linguistic rules.